Strengthening Basic Education through "Bengkid Study Rolling" with the Method of Reading without Spelling in Probolinggo City - Tumini, Tumini; Hariyanto, Budi; Maulidya, Nabila; Febilina, Novilia Putri; Amrullah, Hamdan (IMPOWERMENT SOCIETY, 2022)
Strengthening education has the aim of improving the quality of human resources in an area. Based on the observations made, several cases of delay in reading ability have been found in the category of high grade elementary school children. With these problems, we provide a solution by holding the "Bengkid Study Rolling" program. This community service activity aims to improve the quality of human resources, especially in reading skills. The obstacles experienced by children on average are difficulty reading syllables and consonants, the method of reading without spelling is one of the effective reading solutions and according to children's needs because learning is designed in a fun way but still firm and straightforward in learning.